1987
DOI: 10.2527/jas1987.652481x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sarsaponin on Growth, Feed and Nitrogen Utilization in Growing Male Rats Fed Diets with Added Urea or Protein

Abstract: Two experiments were conducted with growing male rats to determine the effects of 120 ppm of dietary sarsaponin (S) on nitrogen (N) metabolism when urea or protein are added to the diet. Growth, feed efficiency, N digestibility and balance, urinary N and ammonia-N (NH3-N), and cecal urease and NH3-N were measured. Growth and feed utilization were unaffected by dietary S. Adding urea or protein to the diet increased apparent N digestibility and increased urinary-N excretion. Urea did not affect N balance, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 2 publications
4
17
0
2
Order By: Relevance
“…Lowe & Kershaw (1997) also found no changes in hematological counts. For rats, Preston et al (1987) have found that the use of The initial concentration of total ammonia decreases as zeolite is added; however the data behavior presented in this study are supported by the finding of Sonnenholzner (2004), which showed that the adsorbents are more effective when there is high concentration of solute related to the adsorbent. The authors found, by including 1 g zeolite, the removal of total ammonical-N at 1.53 mg/g.…”
Section: Resultssupporting
confidence: 40%
See 1 more Smart Citation
“…Lowe & Kershaw (1997) also found no changes in hematological counts. For rats, Preston et al (1987) have found that the use of The initial concentration of total ammonia decreases as zeolite is added; however the data behavior presented in this study are supported by the finding of Sonnenholzner (2004), which showed that the adsorbents are more effective when there is high concentration of solute related to the adsorbent. The authors found, by including 1 g zeolite, the removal of total ammonical-N at 1.53 mg/g.…”
Section: Resultssupporting
confidence: 40%
“…The reduction in the odor can be achieved through the use of raw materials with high digestibility. This effect can be enhanced by the use of additives such as Yucca schidigera extract, which inhibits the urease by the extract's saponin fraction (Preston et al, 1987) and is an alternative source of fiber, which helps in reducing the intestinal transit (McFarlane & Metheney, 1998); or with the inclusion of zeolite (hydrated aluminum silicates), which has properties such as adsorption of gas, fumes and water (Pond et al, 1995) that, somehow, will act on the mechanisms that contribute to the bad odor in feces. Currently, there is a great scientific interest in the usage of both Yucca schidigera extract (YSC) and zeolite, additives classified as odor reducers (Anfalpet, 2008), due to their extensive range of functional properties.…”
Section: Introductionmentioning
confidence: 99%
“…Week of feeding had no effect on fecal TKN (P 5 0.585), urinary TKN (P 5 0.848), or urinary NH 4 1 -N (P 5 0.747; Table 3). Yucca extract was once believed to exert its effects on ammonia volatilization through inhibition of urease by its saponin fractions (Preston et al, 1987). However, because the magnitude of its effects are much too great to be completely explained by its only weak inhibitory properties (Killeen, 1995) and because liberation of radioactively labeled carbon dioxide of urea origin by jack bean urease was not impaired by yucca (Headon et al, 1991), the mode of action of yucca extract is now believed to be through a binding or conversion of ammonia (Headon et al, 1991).…”
Section: Excreta Compositionmentioning
confidence: 99%
“…Esses benefícios também podem ser alcançados com a inclusão na dieta de aditivos como o extrato de Yucca schidigera, que inibe a urease pela fração de saponinas do extrato (Preston et al, 1987) e é fonte alternativa de fibra, auxiliando na redução no trânsito intestinal (McFarlane et al, 1988a), ou com a inclusão de zeólitas (aluminiossilicatos hidratados), que têm propriedades de absorção de gases, vapores e água (Pond et al, 1995).…”
Section: Introductionunclassified